Intravenous clevidipine for management of hypertension - Alma Rivera; Elsa Montoya; Joseph Varon (Dove Medical Press, 2010)
Alma Rivera1, Elsa Montoya2, Joseph Varon31Universidad Autónoma de Chihuahua, Chihuahua, México; 2Universidad de Monterrey, Nuevo León, México; 3University of Texas Health Science Center at Houston, Texas, USAAbstract: Hypertension remains one of the most prevalent diseases affecting our society, and its complications lead the list of causes of mortality all over the world. Most efforts to control the disease are unsuccessful, failing in at least two-thirds of affected patients, despite the availability of multiple drugs for its treatment. The limited number of medications available for aggressive management of hypertensive crises has intensified the search for novel drugs that can achieve a rapid decrease in blood pressure without increasing the possible complications. Clevidipine is a novel, vasculoselective, dihydropyridine calcium channel blocker characterized by a very fast onset and offset of action. Metabolism of clevidipine does not occur in the liver or kidneys, and thus there are no restrictions to using clevidipine in patients with hepatic or renal dysfunction. This agent has been widely used to reduce blood pressure when oral therapy is not appropriate, and its use in the perioperative setting has been shown to be beneficial. This manuscript reviews the key characteristics of clevidipine and its role in the management of acute hypertension.Keywords: clevidipine, hypertension management, acute, hypertensive crises, intravenous